Ash melting behaviour of reed and woody fuels blends. (15th April 2022) - Link, Siim; Yrjas, Patrik; Lindberg, Daniel; Trikkel, Andres; Mikli, Valdek
Highlights: The addition of reed to woody fuel changes the ash melting behaviour. The chemical modelling could predict melting onset at too low temperatures. Feldspars in wood chips could cause the sluggish melting process of ash. Abstract: Ash melting behaviour is an important issue regarding operation of boilers, for instance, to avoid the agglomeration of the fluidized bed. Previous studies have shown that ash melting behaviour of the blends could differ from that of single parent fuels. This study focuses on the melting behaviour of fuel ash blends of reed, pine wood pellets and Douglas fir wood chips. For that purpose, simultaneous thermal analysis, heating microscope and scanning electron microscopy with energy dispersive X-ray analysis, X-ray diffraction, and FactSage modelling were used. The ash sample was heated up to the final temperatures stepwise, and the morphology and composition of the ash samples were examined at different temperatures. The results revealed that the melting onset for reed and woody fuels blend ashes was related to KCl-K2 SO4 eutectic. The melting started at 700 °C and chlorine was released. The decomposition of CaCO3 was observed for the ashes containing wood pellets. In the case of reed and wood pellet ash, both processes performed simultaneously. The second mass loss and sulphur release were observed at 1100 °C, which is related to decomposition of K2 SO4 . In reed and woody fuels blend ashes, the gas release was accompanied with the melting of other substances (e.g. Si-Ca or Si-Ca-K system) and the gases were trapped into melt. The feldspars abundant in Douglas fir wood chips, could cause the sluggish melting behaviour of ash material. The FactSage modelling indicated the melting onset at lower temperatures compared to the results obtained by the other methods applied.